Entre lógicas e astúcias: a poética da vingança num certo Abril despedaçado - Silva, Igor Monteiro (2009)
About the tension between the institutions and their "users", about strategic calls and tactical deviations, about logics and cunnings, it´s that the present work seeks be structured. Having as reference Michel de Certeau´s conceptions, this dissertation takes Abril Despedaçado film as a investigation field, trying to think about revenge practices and their effects on them involved in the family contentions. Therefore, know that does such practice an institution, analyze their constituent elements and, above all, examine the ways like it is consumed by the habitants of Riacho das Almas - place of the interior baiano, stage of the conflict between Breves and Ferreiras -, are the main objectives. The "reflexivity" made possible by the estrangement and, consequently, the interpellation of the protagonists of the death cycle, is here a reflection object too. It is important to say, that this present work leaves of the idea that the cinema, as aesthetic experience, supplies tracks for understanding the social and cultural world.